Cloud Computing: A Critical Evaluation of Its Revolutionary Potential versus Overhyped Status - Patil, Rupali B. (Journal of Research in Science and Engineering, 2025)
Cloud computing has transformed IT operations by providing scalable, cost - effective, and flexible solutions. This paper explores cloud computing's benefits, challenges, and impact on Management Information Systems (MIS). The discussion includes various cloud service models (SaaS, PaaS, IaaS), security concerns, cost considerations, and managerial challenges. While some believe cloud computing is a revolutionary shift, others argue it is an overhyped trend. This study provides a balanced perspective by analyzing cloud computing's potential and limitations